2015
DOI: 10.1016/j.watres.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen availability influences phosphorus removal in microalgae-based wastewater treatment

Abstract: Microalgae offer a promising technology to remove and re-use the nutrients N and P from wastewater. For effective removal of both N and P, it is important that microalgae can adjust the N and P concentration in their biomass to the N and P supply in the wastewater. The aim of this study was to evaluate to what extent microalgae can adjust the N and P concentrations in their biomass to the N and P supply in the wastewater, and to what extent supply of one nutrient influences the removal of the other nutrient. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(142 citation statements)
references
References 36 publications
10
129
1
2
Order By: Relevance
“…Great phylogenetic differences were observed in growth rate, nutrient removal capacity and preferred habitat among microbial groups (Beuckels et al, 2015;González-Camejo et al, 2017). Liu and Vyverman (2015) reported that the filamentous microalgae Cladophora sp., Klebsormidium sp.…”
Section: Microorganism Selection and Consortium Constructionmentioning
confidence: 99%
“…Great phylogenetic differences were observed in growth rate, nutrient removal capacity and preferred habitat among microbial groups (Beuckels et al, 2015;González-Camejo et al, 2017). Liu and Vyverman (2015) reported that the filamentous microalgae Cladophora sp., Klebsormidium sp.…”
Section: Microorganism Selection and Consortium Constructionmentioning
confidence: 99%
“…Furthermore, the uptake rates and storage may be affected by the culture history and may be increased after starvation (34). For mixed cultures grown under varying influent conditions, the Nto-P ratio may promote growth of one algae species over the others, which can further adapt their nutrient content depending on the cultivation medium (42). The combination of these factors suggests that the algae would be able to take up and store all the incoming nutrients, even if there is some imbalance between them.…”
Section: Discussionmentioning
confidence: 99%
“…In wastewater, nutrients are mostly found in the organic form and as inorganic compounds such as ammonium, nitrate and orthophosphate. Ammonium is the preferred form of nitrogen for algae uptake, while nitrate within the algae cell is reduced back to ammonium and assimilated into amino acids for the synthesis of proteins (Beuckels et al, 2015). Inorganic phosphorous in turn, is utilized for ribosome RNA synthesis.…”
Section: General Performancementioning
confidence: 99%